2010
DOI: 10.5433/1679-0359.2010v31n4p1051
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da linhagem, espaço na gaiola e nível de triptofano dietético no desempenho de poedeiras comerciais

Abstract: ResumoCom o objetivo de avaliar os efeitos da linhagem, do espaço na gaiola e do nível dietético de triptofano sobre o desempenho produtivo de poedeiras comerciais leves foi conduzido um experimento com 720 galinhas de duas linhagens, 360 da linhagem A e 360 da linhagem B, das 31 à 47 a semana de idade. O delineamento experimental utilizado foi inteiramente casualizado, em um esquema fatorial 2x3x4 (linhagens comerciais, A e B, espaço na gaiola, 563, 450 e 375 cm 2 /ave e nível dietético de triptofano, 0,175; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Conversely, in all treatments where Ile was supplemented, hens showed similar performance and egg quality as layers that received diet supplementation with all three of the studied AA, indicating that Ile is a potentially limiting AA in low-CP diets for laying hens. This confirms the results found by other authors (SHIVAZAD et al, 2002;PEGANOVA;EDER, 2003;RECH et al, 2010).…”
Section: Resultssupporting
confidence: 83%
“…Conversely, in all treatments where Ile was supplemented, hens showed similar performance and egg quality as layers that received diet supplementation with all three of the studied AA, indicating that Ile is a potentially limiting AA in low-CP diets for laying hens. This confirms the results found by other authors (SHIVAZAD et al, 2002;PEGANOVA;EDER, 2003;RECH et al, 2010).…”
Section: Resultssupporting
confidence: 83%
“…These results are in agreement with previous trials, which also described no effect of rearing density on weight gain (PATTERSON; SIEGEL, 1998), body weight and flock uniformity (PAVAN et al, 2005) of pullets during the first weeks of life. On the contrary, Rech et al (2010) concluded that the reduction on floor space provided for birds significantly impairs weight gain. Differences in the values of floor space analyzed in each work could explain these discrepant results.…”
Section: Resultsmentioning
confidence: 99%